Combined effect of linezolid and N-acetylcysteine against Staphylococcus epidermidis biofilms - Leite, Bruna; Gomes, Fernanda; Teixeira, Pilar; Souza, Clovis; Pizzolitto, Elisabeth; Oliveira, Rosário (My University, 2013)
Introduction: Staphylococcus epidermidis is an organism commonly associated with infections caused by biofilms. Biofilms are less sensible to antibiotics and therefore are more difficult to eradicate. Linezolid and N-acetylcysteine (NAC), have demonstrated to be active against gram-positive microorganisms. Therefore and since linezolid and NAC have different modes of action, the main objective of this work was to investigate the single and synergistic effect of linezolid and NAC against S. epidermidis biofilms. Methods: This work reports the in vitro effect of linezolid and NAC against S. epidermidis biofilms, treated with MIC (4 mg ml-1) and 10×MIC of NAC, and MIC (1 μg ml-1) and peak serum concentration (PS = 18 μg ml-1) of linezolid alone and in combination. After exposure of S. epidermidis biofilms to linezolid and/or NAC for 24 h, several biofilm parameters were evaluated, namely the number of cultivable cells [colony forming unit (CFU) enumeration], total biofilm biomass and cellular activity. Results: When tested alone, NAC at 10×MIC was the most effective agent against S. epidermidis biofilms. However, the combination linezolid (MIC) + NAC (10×MIC) showed a synergistic effect and was the most biocidal treatment tested, promoting a 5 log reduction in the number of biofilm viable cells. Conclusion: This combination seems to be a potential candidate to combat infections caused by S. epidermidis biofilms, namely as a catheter lock solution therapy. © 2012 Elsevier España, S.L. All rights reserved.
Keywords: Antimicrobial agents; Biofilm; Linezolid; N-acetylcysteine; Staphylococcus epidermidis